The plans of senior students after graduation and the factors that affect them - Belacaol, Charity; Diomo, Anne Marie; Gabinete, Richelle; Juanitas, Benelle; Lopez, Rani; Sarabia, Beverly
This study was conducted through surveys to find out the plans of senior students of the College of Management after graduation. In this study, the respondents are considered the independent variable and the dependent variable. The research presented various plans of graduating students such as applying for work, attending family business, taking a much needed vacation, getting married and enrolling in an academic program. The result of this statistical analysis showed that 75 percent of the graduating UPV CM students plan of applying for work after graduation. This could be contributed because of the present economic situation of the country and basically they want to help their family as well as themselves. Most respondents are from Iloilo so half or 50 percent preferred to work in Iloilo as well. Accessibility, near boy/girl friend, life style, job opportunity, high salary, cheaper standard of libing are the reasons why they preferred to chose such place to work. Half or 50 percent of the respondents chose accessibility as their main consideration in choosing a place to work. the 58 percent choose to work in public organization. Statistics show that 15 percent of the respondents want to take a much-needed vacation, five percent wants to get married and another five percent plans to enroll in an academic program. Academic programs such as Master's Degree and law are highly preferred by the respondents. Parents, relatives, teachers, and friends were considered as persons who influenced such decision. Based on the survey 45 percent of the respondents answered that parents are the most influential persons in their decision-making.